2022
DOI: 10.1002/cncy.22630
|View full text |Cite
|
Sign up to set email alerts
|

Ki‐67 index assessment on FNA specimens of gastrointestinal stromal tumor: Correlation with mitotic rate and potential predictive value for risk stratification

Abstract: BACKGROUND: Risk assessment of gastrointestinal stromal tumor (GIST) is challenging on cytology specimens. This stud y aims to determine whether Ki-67 index evaluated on fine-needle aspiration (FNA) specimens can correlate with the mitotic rate of GIST in surgical specimens and provide further risk assessment. METHODS: Cases with cell blocks containing adequate tumor cells and surgical resections were included. Ki-67 immunostain was retrospectively performed on cell block sections, and Ki-67 index was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition, the Ki-67 PI of several samples were acquired from fine needle aspiration specimens, which could lead to potential bias considering the heterogeneity in Ki-67 PI values. Nevertheless, a previous study has demonstrated good correlation between FNA-based Ki-67 PI and mitotic count in surgical specimens, and we have determined that fine needle aspiration can be used for Ki-67 PI assessment in GISTs [27]. Lastly, our use of three-dimensional VOI for tumor segmentation is time-consuming and subject to debate regarding inter-reader variability.…”
Section: Study Limitationsmentioning
confidence: 92%
“…In addition, the Ki-67 PI of several samples were acquired from fine needle aspiration specimens, which could lead to potential bias considering the heterogeneity in Ki-67 PI values. Nevertheless, a previous study has demonstrated good correlation between FNA-based Ki-67 PI and mitotic count in surgical specimens, and we have determined that fine needle aspiration can be used for Ki-67 PI assessment in GISTs [27]. Lastly, our use of three-dimensional VOI for tumor segmentation is time-consuming and subject to debate regarding inter-reader variability.…”
Section: Study Limitationsmentioning
confidence: 92%